Süleymaniye Kütüphanesinde bulunan bir Maktel-i Âl-i Resûl (Hacı Mahmud Efendi, nr. 4724) - Özil, Sibel (My University, 2018)
Maktel-i Hüseyin yazma geleneği, vak’anın vukûundan günümüze kadar varlığını sürdürmüş ve edebiyatımızda birçok isim Hz. Hüseyin’in şehâdetini etkili bir biçimde kaleme almıştır. Süleymaniye Kütüphanesinde Bulunan Bir Maktel-i Âl-i Resûl (Hacı Mahmud Efendi, nr. 4724) başlıklı bir maktel-i Hüseyin çalışması olan bu tezin amacı, maktel-i Hüseyin geleneğini canlı tutmak ve bu vesîle ile yazma eser kütüphanelerinde unutulan eserlerimizi gün ışığına çıkarmaktır. Çalışmanın giriş kısmı, araştırmacılara fayda sağlaması ümidi ile maktel-i Hüseyin’ler ile ilgili bir bibliyografya denemesine ayrılmıştır. Üç bölümden oluşan tezin birinci kısmı, ilgili eserin şekil ve muhtevâ özelliklerine hasredilmiş, ikinci kısımda ilgili eser ile tür içerisinde benzer üç çalışmanın kıyası yapılmıştır. Üçüncü bölüm ise nüsha tavsifi, transkripsiyonlu metin ve nüshaların tenkitli neşrine ayrılmıştır

The tradition of writing maktel-i Hussein, has been written since it happened and many distingushed writers in the literature have touchily indited Hussein’s martyrdom. The main purpose of this thesis, a study of a manuscript on maktel-i Hussein named as A Maktel-i Âl-i Resûl in Süleymaniye Library (Hacı Mahmud Efendi no 4724), is to keep alive the spirit of The tradition of writing of maktel-i Hussein and herewith bring to light our written tradition which are unfortunately forgotten as manuscripts in libraries. This work consists of four chapters, an introduction, devoted to a bibliography essay regarding maktel-i Hussein with the hope that future researchers will benefit from it, three chapters. The first chapter includes the shape and content features of the related manuscript. In the second chapter the manuscript and are compared with three similar studies on the same topic. The last chapter is devoted to introduction of the manuscripts, transcriptional text and criticism of the manuscript.
Keywords: Edebiyat; History and criticism; Islamic literature, Turkish; İslam edebiyatı, Türk; Karbala; Kerbelâ; Maktel; Maktel-i Hüseyn; Maktel-i Hüseyn Literature; Tarih ve eleştiri; Turkish literature; Türk edebiyatı